Land use change projection and driving factors exploration in Hainan Island based on the PLUS model - Liu, Jiahui; Hou, Yaoqi; Li, Fangyi; Zheng, Binbin; Chen, Zeheng; Zheng, Fa; Zhang, Xiaohai; Yu, Rui (Frontiers in Marine Science, 2025)
IntroductionLand resources play a vital role in national economic and social development. Hainan Province faces the challenge of balancing land use with conservation while striving to develop a high-quality free trade port. This study aims to analyze land use changes and their driving factors to support sustainable land use policies.MethodsThis study utilised the GlobeLand30 dataset, along with data on temperature, precipitation, the digital elevation model (DEM), slope, soil, gross domestic product (GDP), and population, to apply the Patch-generating Land Use Simulation (PLUS) model. This model was used to analyse land use changes on Hainan Island from 2000 to 2020, to investigate the relationship between land use change and its driving factors.Results(1) During 2000 2020, forests and cultivated land were the predominant land use type, while wetlands and artificial surfaces increased by two times, and bare land remained stable; (2) Temperature significantly influenced cultivated land, forests, and grasslands, while GDP and population growth impacted water bodies and artificial surfaces; (3) The predicted land use map for 2020 achieved high accuracy (Kappa = 0.85); (4) By 2040, forests and cultivated land are expected to remain dominant, with grasslands and artificial surfaces decreasing, while wetlands and bare land are projected to increase.DiscussionThe study highlights the complex interactions between land use and its driving factors in Hainan. The findings provide valuable insights for sustainable land use policy development, balancing economic growth with ecological conservation in the region.